Measuring the Contribution of Strategic Commodities to Persistent Inflation; An Effort to Stabilize the Economy - Farid Abidin; Lustina Fajar Prastiwi (Fakultas Ekonomi dan Bisnis Islam UIN Alauddin Makassar, 2023)
This study aims to analyze the inflation persistence level of the spending group in Blitar Regency and the contribution of 11 commodities or goods/services groups to the formation of inflation persistence in Blitar Regency. In addition, this study also looks at the role of the Regional Inflation Control Team (TPID) in controlling inflation in the regions. This study uses monthly inflation time series data and CPI for 11 commodity groups in Blitar Regency from 2020 to 2020 to 2020 s.d. 2022 obtained from the Blitar Regency Central Bureau of Statistics and publications from Bank Indonesia, the estimation method in this study uses the Univariate Autoregressive Model (AR) and Partial Adjustment Model (PAM) approaches. The results of the study prove that inflation in Blitar Regency has a high level of persistence which is reflected in the time it takes for inflation to return to its equilibrium level, which is 19 months. The persistence of inflation in Blitar Regency was influenced by shocks that occurred in the housing, water, electricity, gas, and fuel group as well as the transportation group as a representative of the administered prices component and the food, beverage, and tobacco group as a volatile food component. group. This research implies that this research can be used as a reference in determining the right time in determining policies by the government, especially in the regulated price group. In addition to controlling inflation in volatile food components due to shocks such as bad weather, TPID can collaborate with relevant agencies to use technology to minimize the impact of climate change and maximize the potential of regional superior products/commodities, and maximize production to maintain supply availability.